Supercapacitor carbon pipe/molybdenum carbide combination electrode material and preparation method thereof - TU JIANGPING; ZHAN JIYE; WANG XIULI; XIA XINHUI; ZHONG YU (2016)
The invention discloses a supercapacitor carbon pipe/molybdenum carbide combination electrode material and a preparation method thereof. Through a hydrothermal method, a zinc oxide template is generated, the zinc oxide template is taken as a carrier, through glucose hydrothermal carbonization, a reaction lasts for 2 to 6 hours, a carbon tube is generated at the upper surface of the zinc oxide template, through a cathode electrodeposition method, a reaction lasts for 5 to 25 minutes, high-temperature heat processing is performed under argon protection, and thus the supercapacitor carbon pipe/molybdenum carbide combination electrode material is prepared. The electrode material comprises a substrate, a nanometer carbon tube arranged on the substrate and a molybdenum carbide nanometer layer coating the nanometer carbon tube. The diameter of the nanometer carbon tube is 80 to 500nm, and the thickness of the molybdenum carbide nanometer layer is 50 to 100nm. The combination material provided by the invention has hi